PsycEXTRA Dataset 1998
DOI: 10.1037/e664862007-001
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of a Wayside Horn at a Highway-Railroad Grade Crossing

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed and completing and reviewing the collection of information. Send comments regarding this burden estimate or any aspects of this collection of information , including suggestions for reducing this burden to Washington Headquarters Service, Directorate for information Operations and Reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…These results are similar to a study of aircraft noise by Rylander, et al (1980). Finally, a recent study by Multer and Rapoza (1998) evaluates community impacts from wayside horns (i.e., horns that are placed in a fixed location as opposed to a moving train) versus train horns. They found lower levels of reported annoyance for wayside horns, which were approximately 13 dB quieter than train horns.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…These results are similar to a study of aircraft noise by Rylander, et al (1980). Finally, a recent study by Multer and Rapoza (1998) evaluates community impacts from wayside horns (i.e., horns that are placed in a fixed location as opposed to a moving train) versus train horns. They found lower levels of reported annoyance for wayside horns, which were approximately 13 dB quieter than train horns.…”
Section: Introductionsupporting
confidence: 75%
“…Note that a crossing is classified as a Conrail crossing if Conrail maintains it, or if any Conrail trains travel through the crossing. Multer and Rapoza (1998) report that locomotive engineers begin sounding their horn approximately 1,320 feet (i.e., a quarter mile) from the highway-railroad grade crossing. In addition, they report that the impact or severe impact zone for train whistles is, at most, 1,000 feet from the train, so an operational definition of an impact zone of properties within 2,320 feet of a rail crossing is adopted.…”
Section: Structure Neighborhood Time Sold Railroadmentioning
confidence: 99%
“…In one study, Multer and Rapoza (1998) examined the effectiveness of wayside horns mounted at three gated grade crossings in Gering, Nebraska. In 1995, driver behavior at two of the three grade crossings was videotaped for a period of 12 weeks before and after the installation of the wayside horn.…”
Section: Locomotive Hornmentioning
confidence: 99%
“…The acoustic data collected in the field by Multer and Rapoza (1998) and Gent, et al (2000) and in the laboratory by Keller and Rickley (1992) all indicated that the wayside horn systems was less audible than the train horn. The wayside horn systems evaluated in these three studies were developed by Railroad Controls Limited (RCL).…”
Section: Locomotive Hornmentioning
confidence: 99%
See 1 more Smart Citation